2015
DOI: 10.1586/14760584.2015.1064772
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles and vaccine development

Abstract: Mucosal vaccines constitute an advantageous immunization approach to achieve broad immunization against widespread diseases; however, improvements in this field are still required to expand their exploitation. As gold nanoparticles are biocompatible and can be easily functionalized with antigens, they have been proposed as carriers for the delivery of vaccines. The study of gold nanoparticles (AuNPs) in vaccinology has been of interest for a number of research groups in recent years and important advances have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 115 publications
0
42
0
2
Order By: Relevance
“…A wide range of molecules, including adjuvants and antigens can be conjugated on AuNPs at high density, resulting in improved immunogenicity and antigen presentation (157,158). AuNPs can be formulated for intranasal administration and can diffuse into the lymph nodes, triggering robust antigenspecific cytotoxic T-cell immune responses (159,160). Tao and coworkers have demonstrated that the peptide consensus M2e of influenza A viruses with a non-native cysteine residue at the C-terminal end could be attached on the AuNPs via thiolate-Au chemistry.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…A wide range of molecules, including adjuvants and antigens can be conjugated on AuNPs at high density, resulting in improved immunogenicity and antigen presentation (157,158). AuNPs can be formulated for intranasal administration and can diffuse into the lymph nodes, triggering robust antigenspecific cytotoxic T-cell immune responses (159,160). Tao and coworkers have demonstrated that the peptide consensus M2e of influenza A viruses with a non-native cysteine residue at the C-terminal end could be attached on the AuNPs via thiolate-Au chemistry.…”
Section: Inorganic Nanoparticlesmentioning
confidence: 99%
“…An antigen, once adsorbed or encapsulated by nanoparticles, may be used as an adjuvant for optimization of the immune response aer vaccination. [97][98][99][100][101][102] In 1986, Japanese researchers 103 rst reported success in generating antibodies against glutamate by using colloidal gold particles as a carrier. Subsequently, a number of papers were published whose authors applied and further developed this technique to obtain antibodies to the following haptens and complete antigens: amino acids; 104 142 In all these studies, the haptens or complete antigens were directly conjugated to colloidal gold particles, mixed with complete Freund's adjuvant or alum, and used for animal immunization.…”
Section: Production Of Antibodies By Using Gold Nanoparticlesmentioning
confidence: 99%
“…18 Antigen-AuNP conjugates, as alternative display vectors to produce highly effective and safe vaccines, show advanced perspectives of greater synthetic control and higher density than on current vector materials such as proteins, peptides/lipopeptides and dendrimers. 19,20 Besides, these materials other than gold may cause immune responses and produce undesired antibodies which decreases the efficiency of vaccinations. 21,22 Owing to the straightforward surface functionalization and excellent biocompatibility, AuNPs do not cause undesired immune response (AuNPs do not elicit the production of antibodies).…”
Section: Introductionmentioning
confidence: 99%